Posture and corporal equilibrium: a study of existents relations - Campelo, T. S.; Bankoff, A. D. P.; Barros, D. D.; Ciol, P.; Zamai, C. A.; Bekedorf, R. G. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
Introduction The postural control system presents aspects related to the postural orientation, witch is the maintenance of the body segments in relation with it self and with the environment, and the corporal equilibrium, witch are the relations between in and out forces that act over the human body to get a corporal equilibrium during the motors actions[1]. These events are composed of distinct phenomenon, although, there are dependents relations between them[2]. Methodology There was selected 16 sedentary individuals, age between 29 and 51 years old, and they wore submit in Ttwo different tests. The first one was the computer postural analysis from Micromed Biotechnology, 3.0 version, witch is a system of body image caption with some anatomic points marked witch gives angles related with the body posture. The second technique was the Electronic Baropodometer From Physical Support Italy, collecting data from the corporal equilibrium of the individuals. The tests were with monopodalic and bipodalic, both were tested with closed and open eyes, during five seconds each. The statistics analyses were done correlating data from posture and corporal equilibrium using the Person correlation from the Statistical 5.0 software. Results The data shows that there are no significant correlation between the posture and the corporal equilibrium using p<0,05. Only on the correlation between the gluteal line and the left monopodailc closed eye was significant statistically. In the corporal equilibrium was verified a bigger oscillation in monopodalic with closed eye. Discussion and Conclusion The equilibrium is extremely influence by vision, due to this posture stability is more difficult with eye closed[3]. A proper posture is indispensable for a good equilibrium, however, a wrong posture does not result necessarily in an equilibrium disturb[4]. The determination of an importance percentage for the afferent system is extremely hard and the global system is so adaptable that a blind individual can maintain his equilibrium with very little precision lost[5].